Paradiso - Dante Alighieri 1265-1321; Hollander, Robert 1933-; Hollander, Jean 1928- (New York Anchor Books, 2008)
"With his journeys through Hell and Purgatory complete, Dante is at last led by his beloved Beatrice to Paradise. Where his experiences in the Inferno and Purgatorio were arduous and harrowing, this is a journey of comfort, revelation, and, above all, love-both romantic and divine. Robert Hollander is a Dante scholar of unmatched reputation and his wife, Jean, is an accomplished poet. Their verse translation with facing-page Italian combines maximum fidelity to Dante's text with the artistry necessary to reflect the original's virtuosity. They have produced the clearest, most accurate, and most readable translation of the three books of The Divine Comedy, with unsurpassable footnotes and introductions, likely to be a touchstone for generations to come."
Translated from the Italian.
"The Hollander translation is the text for the Princeton Dante Project"--Page [4] of cover.
Includes bibliographical references (pages [957]-989) and indexes.
Parallel texts in Italian and English.
Keywords: Dante Alighieri -- 1265-1321.; Heaven -- Poetry; Paradise in literature; Italian poetry -- 14th century